PVA/Stevia/MIL-88A@AuNPs composite nanofibers as a novel sorbent for simultaneous extraction of eight agricultural pesticides in food and vegetable samples followed by HPLC-UV analysis. (30th August 2022) - Hejabri kandeh, Saeed; Amini, Shima; Ebrahimzadeh, Homeira
Highlights: A new electrospun composite based on poly(vinyl alcohol) was fabricated. Au nanoparticles improve the density of MIL-88A active sites. MIL-88A@Au nanoparticles increase porosity of nanofibers. The developed method provided low limits of detection for target pesticides. This method is eco-friendly thanks to low organic solvent and sorbent consumption. Abstract: Herein, an electrospun composite from poly(vinyl alcohol) (PVA) and Stevia extract as a cross-linked nanofibrous was prepared with incorporating Fe-metal organic framework@Au nanoparticles (MIL-88A@AuNPs). The final composite was characterized, and then used as an efficient sorbent in pipette-tip micro solid-phase extraction (PT-µSPE) of eight selected pesticides in food samples followed by HPLC-UV analysis. Under the opted conditions, the linearity was in the range of 1.0–1000.0 ng mL −1 for atrazine and ametryn, 3.0–1500.0 ng mL −1 for tribenuron-methyl, metribuzin, profenofos and chlorpyrifos, 5.0 to 1500.0 ng mL −1 for phosalone, and 5.0–2000.0 ng mL −1 for malation with coefficient of determination (r 2 ) ≥ 0.9943. The LODs (based on S/N = 3) ranged from 0.3 to 1.5 ng m L −1 . The relative standard deviations (RSDs) were between 5.2% and 6.6% (intra-day, n = 5) and 5.9%-7.4% (inter-day, n = 3) for three consecutive days. Ultimately, the capability of the method in various food samples was appraised with good recoveries (79.3 to 97.6%).